PERAN KOMUNITAS MIKROBA LUMPUR AKTIF DALAM PEROMBAKAN DETERGEN ALKIL SULFONAT LINEAR DAN BENZENA ALKIL SULFONAT - I Made Sudiana (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2004)
The study was conducted to evaluate the biodegradation of detergent contained Alkyl Sulfonate (LAS) and Benzene Alkyl Sulfonate (BAS) occur under aerobic condition by complex microbial community in activated sludge process. A 1.8 L of sequential batch reactor, and batch experiments were set up to study the characters LAS and BAS biodegradation. Microbial community in Activated Sludge actively brook down LAS and BAS. Biodegradation rate of LAS was higher than that of BAS. The complex chemical molecule structure of ABS could be the reason for slower degradation of BAS. The value of LAS degradation under aerobic condition were indicated by μmax of 0.26–h, Ks = 15.5 mg/L, Vmax = 11.04 mg/L. hour–1and Km = 8.19 mg/L. Whereas for BAS were μmax of 0.22–h, Ks = 25.1 mg/L, Vmax = 12.74 mg/L. hour–1and Km = 8.119 mg/L. Activated sludge process is appropriate technology for removal of removal of LAS and BAS.